Cross-Cultural Communication: Linguistic and Cultural Dimensions â Implications for the Language Classroom - Gloria Poedjosoedarmo (TEFLIN Journal: A publication on the teaching and learning of English, 2005)
Abstract: Differences in cultural perspectives can be one of several posÂsible causes for communication breakdowns in cross-cultural communicaÂtion. This paper will attempt to classify possible causes for communicaÂtion breakdown and explore sorts of knowledge and skills students need to avoid these situations, as well as classroom activities that can develop the needed knowledge and skills.